2006
DOI: 10.1111/j.1600-0854.2006.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins but not Compactin Inhibit the Lateral Diffusion of Membrane Proteins Independent of Cholesterol

Abstract: Cholesterol and glycosphingolipid-enriched membrane domains, termed lipid rafts, were proposed to play important roles in trafficking and signaling events. These functions are inhibited following putative disruption of rafts by cholesterol depletion, commonly induced by treatment with methyl-beta-cyclodextrin (MbetaCD). However, several studies showed that the lateral diffusion of membrane proteins is inhibited by MbetaCD, suggesting that it may have additional effects on membrane organization unrelated to cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 67 publications
5
64
0
Order By: Relevance
“…Nevertheless, this study also found that BACE1 processing of APP is inhibited with further loss of cholesterol (Ͼ35%), consistent with earlier studies (32,33). Nevertheless, given the pleiotropic effects of cholesterol depletion on membrane properties and vesicular trafficking of secretory and endocytic proteins (42)(43)(44)(45)(46)(47), unequivocal conclusions regarding BACE1 processing of APP in lipid rafts cannot be reached based on cholesterol depletion studies.…”
supporting
confidence: 32%
See 1 more Smart Citation
“…Nevertheless, this study also found that BACE1 processing of APP is inhibited with further loss of cholesterol (Ͼ35%), consistent with earlier studies (32,33). Nevertheless, given the pleiotropic effects of cholesterol depletion on membrane properties and vesicular trafficking of secretory and endocytic proteins (42)(43)(44)(45)(46)(47), unequivocal conclusions regarding BACE1 processing of APP in lipid rafts cannot be reached based on cholesterol depletion studies.…”
supporting
confidence: 32%
“…Moderate loss of cholesterol in hippocampal neurons (Ͻ25% loss) facilitated colocalization of APP and BACE1 and increased A␤ production by promoting BACE1 cleavage of APP. In addition to these apparent discrepancies, proper interpretation of cholesterol depletion studies are confounded by the pleiotropic effects of cholesterol depletion on endocytosis, Golgi morphology, and vesicular trafficking, as well as perturbation in lateral diffusion of raft and non-raft proteins due to alterations in membrane fluidity and curvature (42,43,(45)(46)(47). For example, as cholesterol-rich lipid microdomains are required for the biogenesis of secretory vesicles from the TGN (44), it is highly likely that secretory trafficking of APP, BACE1, and ␥-secretase are all compromised in cells depleted of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…8A-C) (Nishimura et al, 2006). However, a reduction in mobility of non-raft proteins following treatment with MbCD has also been observed Shvartsman et al, 2006;Zidovetzki and Levitan, 2007). These authors have drawn attention to additional effects mediated by MbCD that can include cytoskeletal disruption, depletion of cholesterol from non-raft regions of the PM and effects on other phospholipids.…”
Section: Ac8 Mobility Depends On Membrane Cholesterolmentioning
confidence: 99%
“…Reaction dominant Shvartsman et al 2006). TIR-FRAP was applied to calculate the rates of binding and unbinding of hormones to and from the cell surface (Hellen and Axelrod 1991;Fulbright and Axelrod 1993).…”
Section: Applicationsmentioning
confidence: 99%